2013
DOI: 10.1002/zoos.201300009
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the tribe Chelonini Foerster (Hymenoptera: Braconidae: Cheloninae) of northern Iran, with first records for eight species and an updated check list of Iranian species

Abstract: The tribe Chelonini Foerster (Braconidae: Cheloninae) of northern Iran was studied. The specimens were collected using Malaise traps during 2010 and 2011. A total of 15 species were collected and identified, of which eight species, Ascogaster annularis (Nees, 1816); A. excavata Telenga, 1941; A. grahami Huddleston, 1984; A. kasparyani Tobias, 1976; Chelonus (Chelonus) armeniacus Tobias, 1976; C. (Chelonus) bonellii (Nees, 1816); C. (Chelonus) elongatus Szepligeti, 1898 and C. (Microchelonus) flavipalpis Szepli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Based on the latest checklist of Iranian Braconidae (Farahani et al, 2016), only scattered records of Chelonini from western Iran (Kordestan, Lorestan, Kermanshah, and Ilam provinces) have been published. Farahani et al (2013Farahani et al ( , 2014 studied the tribe Chelonini and reported 12 species from northern Iran. Currently, 67 species of the subfamily Cheloninae are known from Iran, but many are waiting to be discovered (Farahani et al, 2016), considering the number known from the West Palaearctic region.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the latest checklist of Iranian Braconidae (Farahani et al, 2016), only scattered records of Chelonini from western Iran (Kordestan, Lorestan, Kermanshah, and Ilam provinces) have been published. Farahani et al (2013Farahani et al ( , 2014 studied the tribe Chelonini and reported 12 species from northern Iran. Currently, 67 species of the subfamily Cheloninae are known from Iran, but many are waiting to be discovered (Farahani et al, 2016), considering the number known from the West Palaearctic region.…”
Section: Introductionmentioning
confidence: 99%
“…comm.). A serie of taxonomic works have been done on the Iranian Cheloninae (Lashkari Bod et al, 2011;Ameri et al, 2012;Farahani et al, 2013Farahani et al, , 2014, but nothing is well documented on Adeliini.…”
Section: Introductionmentioning
confidence: 99%